Modified V-I droop based adaptive vector control scheme for demand side management in a stand-alone microgrid. (September 2021) - Jha, Sumit Kumar; Kumar, Deepak; Lehtonen, M.
Highlights: Developed an advanced modified V-I droop strategy to exhibit demand side management. Proposed scheme ensures voltage levels at all buses well within IEEE-Standard range. Developed a new approach to determine value of droop gain coefficient for V-I droop. Performance of proposed scheme is validated under different contingent conditions. Abstract: The concept of conservative voltage reduction (CVR) is widely adopted in the distribution sector to curtail the load demand with the regulation of bus voltage to the lower value. The reduction of the peak demand and energy saving are the two key attributes furnished by implementing the CVR strategy. The voltage source inverter (VSI) based AC microgrid enables the integration of renewable energy sources (RES) to the AC network. Apart from facilitating the process of power generation, the VSI enabled renewable energy sources conducts the ancillary service such as demand side management (DSM) with the enforcement of CVR. The CVR's applicability for demand side management considered to be prospective research for stand-alone microgrid. However, least exploration is being conducted in this direction for autonomous microgrid and hence, the paper is intended to investigate CVR's performance on VSI enabled stand-alone microgrid. A 2-degree of freedom enabled adaptive vector control is being utilized to synchronize the frequency parameter of the microgrid network which utilizes the set parameter of static and transient droop gain function. A new approach is devised to compute the droop parameter for V-I droop which performs CVR action to realize demand side management. The proposed strategy utilizes the voltage reduction mechanism to establish voltage at the load side with the coordination of high and low bandwidth controller. The verification of the proposed work is established with 5 bus microgrid test system and further, three phases to ground fault condition is being put on the controller to test its adequacy. The simulation results are furnished through MATLAB/Simulink software.